A Dedicated Spanish Language Line Increases Enrollment of Hispanics Into Prehospital Clinical Research. Issue 5 (May 2017) - Sanossian, Nerses; Rosenberg, Lauren; Liebeskind, David S.; Starkman, Sidney; Eckstein, Marc; Stratton, Samuel; Pratt, Franklin D.; Hamilton, Scott; Kim-Tenser, May; Sharma, Latisha K.; Restrepo, Lucas; Valdes-Suieras, Miguel; et al.
Abstract : Background and Purpose—: Novel methods are needed to reduce the disparity of Hispanic enrollment in stroke clinical trials. Prehospital enrollment using a dedicated Spanish language line may help overcome this bias. Methods—: Subjects or legally authorized representatives provided information on race and ethnicity for all cases enrolled in the FAST-MAG clinical trial (Field Administration of Stroke Therapy-Magnesium), a prehospital phase 3 randomized study of intravenous magnesium for neuroprotection. One of 2 in-ambulance cell phones (in English or Spanish) was used to obtain informed content in the field. We describe the yield and characteristics of subjects enrolled via Spanish line. Results—: There were 1700 subjects enrolled from 2005 to 2012, of which 402 (24%) identified as Hispanic ethnicity. Study racial makeup was 1325 (78%) white, 219 (13%) black, and 139 (8%) Asian. The dedicated Spanish line was used for 195 (12%) enrollments. Spanish-line enrollments were younger (65 versus 70 years old; P <0.001), more likely to identify as Hispanic (98% versus 14%; P <0.001), and more likely to present with intracerebral hemorrhage (36% versus 21%; P <0.001). Conclusions—: The use of a dedicated Spanish language enrollment line allowed for greater enrollment of Hispanics, a population with significantly different baseline characteristics. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00059332.